2021
DOI: 10.1186/s12872-021-01959-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of vitamin D receptor gene polymorphisms in a cohort of myocardial infarction patients with coronary artery disease

Abstract: Background Vitamin D deficiency is associated with cardiovascular diseases, including coronary artery diseases (CAD). As vitamin D manifests its biological function through its vitamin D receptor (VDR), VDR gene polymorphisms potentially affect VDR functionality and vitamin D activity. Therefore, the objective of this study was to analyze three well-studied VDR gene polymorphisms—Fok1 (rs2228570), BsmI (rs1544410) and Taq1 (rs731236)—in a cohort of CAD patients after acute myocardial infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Patients with coronary heart disease who experienced a cardiac event were genotyped for the VDR polymorphism rs1544410 . Our findings are consistent with those of a previous study [ 29 ], which found that the T/T genotype of the Bsm I (rs1544410) VDR polymorphism is more common among myocardial infarction CAD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Patients with coronary heart disease who experienced a cardiac event were genotyped for the VDR polymorphism rs1544410 . Our findings are consistent with those of a previous study [ 29 ], which found that the T/T genotype of the Bsm I (rs1544410) VDR polymorphism is more common among myocardial infarction CAD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Table 1 summarized the characteristics of the included studies. For the rs2228570 polymorphism, a total of eleven studies were included in the study with 1908 CAD patients and 1923 controls [ 25 27 , 29 – 32 , 34 , 36 ]; ten studies were analyzed for the study including 4210 CAD patients and 10004 controls for the rs1544410 polymorphism [ 11 , 25 , 27 29 , 35 , 36 ]; for the rs731236 polymorphism, 3136 CAD patients and 9501 controls were included [ 25 27 , 29 , 30 , 32 , 33 , 35 ]; for the rs7975232 polymorphism, nine studies were included with 2815 CAD patients and 9460 controls [ 26 , 27 , 29 , 32 , 33 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were finally included in our manuscript [11,[25][26][27][28][29][30][31][32][33][34][35][36]. Table 1 summarized the characteristics of the included studies.…”
Section: The Characteristics Of Included Studiesmentioning
confidence: 99%
“…The study of Raljevic et al, (31) showed a relationship between CAD and the T/T genotype BsmI (rs1544410) and the G/G genotype Taq1 (rs731236) in the VDR gene. In a Chinese population, Pan et al (32) found no link between Fok1 polymorphism and CAD.…”
Section: Discussionmentioning
confidence: 98%